2017
DOI: 10.1097/md.0000000000007942
|View full text |Cite
|
Sign up to set email alerts
|

Higher body weight and distant metastasis are associated with higher radiation exposure to the household environment from patients with thyroid cancer after radioactive iodine therapy

Abstract: There were insufficient data regarding radiation exposure to the household environment from patients with thyroid cancer who received radioactive iodine (RAI) therapy in Asia; we therefore performed the present study at the Chang Gung Memorial Hospital in Keelung, Taiwan.Patients with papillary or follicular thyroid cancer who received 3.7 GBq (100 mCi) RAI were enrolled in this prospective hospital-based study. The enrolled patients were asked to place a thermoluminescent dosimeter in the living room, bedroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Patients and contact factors such as age and gender together with patients' educational level as well as the relation of the contact to the patient had no statistically significant correlation with CRE (p values > 0.05). This goes with what was previously reported by Kuo et al [28] stating that no factor (e.g., age, sex, renal function, and others) had a significant association with radiation exposure to household family members unless they were in close contact with the patient for a long time. Also, our results are in agreement with what was stated by Martin et al [29] who confirmed the absence of a significant correlation between household contacts radiation exposure and patient education level.…”
Section: Discussionsupporting
confidence: 90%
“…Patients and contact factors such as age and gender together with patients' educational level as well as the relation of the contact to the patient had no statistically significant correlation with CRE (p values > 0.05). This goes with what was previously reported by Kuo et al [28] stating that no factor (e.g., age, sex, renal function, and others) had a significant association with radiation exposure to household family members unless they were in close contact with the patient for a long time. Also, our results are in agreement with what was stated by Martin et al [29] who confirmed the absence of a significant correlation between household contacts radiation exposure and patient education level.…”
Section: Discussionsupporting
confidence: 90%
“…[ 19 ] Higher body weight and distant metastases may predict higher radiation exposure from patients after RAI therapy. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%